Models for implementing changes in motivational factors - Małecka, Joanna; Thalassinos, Eleftherios (Business, Management and Economics Engineering, 2025)
Purpose – the purpose of this article is to present a practical model for supporting motivation in an organization and to demonstrate how aligning employees’ needs with strategic objectives increases work effort, engagement, and overall performance. Research methodology – Conceptual development at the intersection of theory and practice has been examined through a narrative review of the relevant literature, in which the significance of Taylor’s and Weber’s theories, along with contemporary approaches advanced by Stoner and Wankel and by Schermerhorn, is emphasized and integrated with the authors’ empirical managerial experience. Findings – effectiveness hinges above all on the correct sequencing of steps in diagnosing needs and implementing motivational changes. A deep understanding of employees’ unmet needs enables the precise selection of support mechanisms, while a tailored, multi-level managerial approach sustains motivation and more closely aligns individual and organizational goals. Research limitations – the model is conceptual and grounded in literature and the authors’ experience; it lacks systematic, large-sample empirical testing and thus may have limited generalizability across industries and cultural contexts. Practical implications – managers can use the model as a step-by-step guide to: assess employee needs, choose appropriate motivational tools, implement changes in the right order, and maintain motivation as an ongoing, continuous process across all organizational levels. Originality/Value – this contribution integrates classic and contemporary motivation theories into a single, actionable process model. Also emphasizes the often-overlooked importance of implementation sequence and continuity, bridging theoretical insights with practical application.